Konstruktivistička didaktika i neurodidaktika u diskursu reformne pedagogije teorijska polazišta, dileme i komparacija - Maras, Nevenka, pedagoginja; Topolovčan, Tomislav; Matijević, Milan, pedagog (2018)
U radu su kritičko-komparativnom i povijesnom analizom definirani, objašnjeni i dovedeni u odnos koncepti konstruktivističke didaktike te neurodidaktike s pravcima i pokretima reformne pedagogije. Analizom je pokazano da su neka od zajedničkih obilježja konstruktivističke didaktike i neurodidaktike vidljiva u nastavnim strategijama kao što su: učenje istraživanjem, učenje rješavanjem problema, suradničko učenje, djelovanju usmjereno učenje, učenje igrom i projektno učenje. Drugim riječima, u okviru onoga što se naziva nastavom usmjerenom na učenika. Ta obilježja nisu (u potpunosti) noviteti proizašli iz tih koncepata. Ukazuje se da su ta didaktička obilježja formirana još prije više od stoljeća u pravcima i pokretima reformne pedagogije. Opravdano je nuditi zaključak da ono što je označeno kao konstruktivistička nastava već postoji oblikovano u reformnoj pedagogiji. Ali, isto je tako opravdano zaključiti da neuroznanstvena istraživanja, osim što nude nove spoznaje o procesima učenja, potvrđuju i didaktičke vrijednosti pravaca i pokreta reformne pedagogije s prijelaza 19. u 20. stoljeće. S obzirom na međusobnu kompatibilnost analiziranih koncepata, poželjno je težiti njihovoj daljnjoj kritičkoj i argumentiranoj sinergiji, a radi unapređenja nastave.
This work elaborates concepts of constructivism and neurodidactics and directions and movements of the reform pedagogy as defined, explained and brought into relations by critical comparative and historical analysis. Primarily, characteristics, definitions and the development of constructivism and neurodidactics have been explained. Special emphasis has been put on current neuroscientific understandings on methods and processes of learning and their implications in didactic theories and their manifestations in the organisation of learning and teaching. The analisys has shown that some of the ground characteristics of constructivism and neurodidactics are visible in learning strategies such as: inquiry-based learning, problem-based learning, collaborative learning, learning-by-doing, play-based learning and project-based learning. In other words, strategies involving student-centred teaching. Apart from these characteristics being common for both constructivism and neurodidactics, they are not entirely novelties that originated from these concepts alone. Further analysis showed that these didactic characteristics have been recognized, i.e. formed more than century ago in the directions and movements of the reform pedagogy. With respect, it is justifiable to conclude that the characteristics that have been deemed as constructivist teaching, are already present in the reform pedagogy. Likewise, it is reasonable to conclude that the neuroscientific research, besides offering new insights on learning processes, also confirm the didactic value of directions and movements of the reform pedagogy at the turn of the 20th century. Given the mutual compatibility of the concepts analysed in this work, further critical and arguments supported synergy is something to aspire to, with the intention of improvement and advancement of the organising of the learning, teaching and instruction processes.
Bilješke uz tekst.
Bibliografske bilješke uz tekst.
Sažetak ; Summary.
Keywords: Didaktika -- Konstruktivizam -- Reformna pedagogija -- Obrazovna neuroznanost -- Nastava